Development of spatially branched woven node structures on the conventional weaving loom. Issue 13 (July 2018) - Fazeli, Monireh; Hübner, Matthias; Lehmann, Theo; Gebhardt, Ulrike; Hoffmann, Gerald; Cherif, Chokri
The increasing need of consistent implementation of lightweight constructions in many technical fields makes the manufacture of near net-shaped node structure to be used in textile-reinforced composites a subject of great interest. The manufacture of the node structure is required to provide a strong node point whilst maintaining the circumference of each adjoining strut. Despite a variety of available methods to produce three-dimensional nodal fabric, the required geometry for the complex nodular connection element has not yet been fully achieved. Furthermore, the available methods have limitations. The developed woven concept in this work allows for maintaining the configuration of the node structure and dimensions of the tubes, especially at the node points. As a result, all tubes positioned at node points are fully open; this is accomplished without distorting the surrounding area once the flat woven node structure is removed from the loom and erected into three-dimensional configuration. In order to produce a three-dimensional structure on a conventional weaving machine, the structure must be flattened in an appropriate way. By using a mathematical algorithm, it is possible to graph the flattened structure precisely. The developed weaving concept and relating calculation are applied to create the weaving plan of the spatial nodal structures, which can be produced on a shuttle weaving loom. The developed concept in this paper will provide repeatable manufacturing of complex node structures by using the conventional weaving loom. The struts of node structures manufactured using this method can be woven at any angle and with spatial arrangements.